Pengenalan Aksara AUD Desa Tanjung Siraisan - Silfa Hafizah Pulungan; Anisah Ramadani; Fatma Sari Anjelina Daulay (Khidmat Almujtamae: Jurnal Pengabdian Masyarakat, 2023)
One area of development in the growth of basic abilities is language development. Language learning for early childhood is directed at the ability to communicate, both orally and in writing (symbolic). To understand symbolic language, children need to learn to read and write. Therefore, learning a language is often divided into two, namely learning language for communication and learning literacy, namely learning to read and write. The right learning for AUD is a learning that contains elements of fun and relates to the world of AUD. Learning by using fun techniques will make it easier for AUD learning to recognize the alphabet and be ready to continue at a higher stage, namely the reading stage.